Let that Sync in: The Effect of Music Reuse on Product Discovery - Luis Aguiar; Zhizhong Chen (CESifo GmbH, 2024)
Digitization has importantly expanded the scope for reusing music in movies, a process known as music synchronization. We use panel data on Netflix and Shazam to estimate the causal effect of music synchronization on the discovery of reused songs. Our results show that songs are substantially more likely to be discovered via Shazam's music recognition algorithm when reused in movies that get more Netflix exposure, even after controlling for song quality. We further show evidence of reuse in movies positively affecting song consumption on the Spotify charts, indicating that movies play a significant role in boosting the demand of reused music. These results have important implications for the policy debate on copyright and fair use and can additionally inform the negotiation of licensing rights between movie producers and music rightholders. They additionally improve our understanding of how innovations enabled by digitization can affect the content industries.
Keywords: 330; copyright; reuse; digitization; recorded music; music synchronization